Learning path : learn to code for the Web. - Williams, Cassidy; Williams, Camryn; Mendoza, Adrian; Andrew, Rachel; Purewal, Semmy; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"Knowing how to code removes a barrier between your designs and the Web. Instead of creating countless Photoshop mockups, or trying to micromanage a web developer's actions, you can take your ideas directly to the Web. In this course, you'll master HTML, CSS, and JavaScript(14)the primary tools for designing sites and web applications(14)and discover what effective design tools they are."--Resource description page.
Introduction to web in HTML, CSS, and JavaScript / Cassidy Williams & Camryn Williams -- CSS for designers / Adrian Mendoza -- Modern Web development with HTML5 and CSS / Rachel Andrew -- Beginning programming with JavaScript / Semmy Purewal.
Presenters, Cassidy Williams, Camryn Williams, Adrian Mendoza, Rachel Andrew, Semmy Purewal.
Title and publication information from resource description page (Safari, viewed March 15, 2016).
Keywords: Web site development; HTML (Document markup language); Cascading style sheets; JavaScript (Computer program language); Web sites -- Design; Electronic books